From Food (Bread) waste to Bioethnol Producation - Rafika HELAIMIA (My University, 2023)
Abstract – A handful of studies and rough estimations confirm that roughly 1.3 billion tons of food get wasted. The staggering volume of food waste management has been shed light and constitutes a significant challenge because of -its environmental, social, and economic impacts. Recent estimates suggest that 8- 10% of global greenhouse gas emissions are due to non-food conception, and the global economic costs of food waste have reached US$750 million per Annam. That is why Sustainable Development Goal 12.3 calls for the importance of food waste management. Wastes of bread represent an important fraction of retail food leftovers. If non-consumed food has been widely valorized in previous years, bread waste is nowadays increasingly of heightened attention. Bread waste can be a promising feedstock for producing bioconversion value-added products. Recently, several technological methods have been reported for the possibility of transforming bread waste into eco-friendly materials such as ethanol, lactic acid, succinic acid, biohydrogen… etc. This study, based on recent research, sheds light on the possibility to convert food waste, especially bread leftovers into bioethanol by using waste bread as the sole source of nutrients for the growth of Aspergillus niger, which produces glucose, and Saccharomyces cerevisiae, which produces ethanol from glucose (i).
Recently, several technological methods have been reported for the possibility of transforming bread waste into eco-friendly materials such as ethanol, lactic acid, succinic acid, biohydrogen… etc. This study, based on recent research, sheds light on the possibility to convert food waste, especially bread leftovers into bioethanol by using waste bread as the sole source of nutrients for the growth of Aspergillus niger, which produces glucose, and Saccharomyces cerevisiae, which produces ethanol from glucose (i)